Impact of cardiovascular disease on health-related quality of life among older adults in eastern China: evidence from a national cross-sectional survey - Wan, Leping; Yang, Guangmei; Dong, Haiying; Liang, Xiaoxiao; He, Yan (Frontiers in Public Health, 2024)
Abstract Objective: This study explores the health-related quality of life (HRQoL) scores of Chinese older adults with Cardiovascular Disease(CVD) using the EQ-5D-3L, the aim of this study is to investigate the association between health and HRQoL in older adults with CVD. Methods: The data for this study were obtained from a cross-sectional study involving older adults residing in Chinese communities The EQ-5D-3L is used to measure the HRQoL scores in the older adults with CVD. One-way analyses were conducted using the Wilcoxon rank sum test and the Kruskal-Wallis H test to assess differences between groups. A binary logistic regression model was employed to analyze the influence each variable has on the presence of "any problem" on each dimension of EQ-5D-3L in older adults with CVD. An ordinal least squares (OLS) model is used to assess the relationship between older adults with CVD and HRQoL. Results: The mean EQ-5D-3L score for older adults with CVD is 0.774. 40.0% of older adults with CVD reported problems with pain/discomfort, followed by Mobility (35.9%), Self-care (31.5%), and Anxiety/depression (17.0%). Binary logistic regression models show that financial resources were the main factor influencing the five dimensions of EQ-5D-3L. The OLS model further indicates that younger age, financial resources, and a lower number of chronic conditions among older adults with CVD are associated with higher HRQoL scores. Conclusions: Chinese older adults with CVD have low HRQoL scores. Variousfactors influence both overall HRQoL scores and scores on each EQ-5D-3L dimension. This study is helpful in enhancing society's attention to the HRQoL of older adults with CVD and taking targeted measures to improve them.